Regulating Strategies of Transcription and Alternative Splicing for Cold Tolerance Harpadon nehereus Fish - Sun, Zhicheng; Huang, Liangliang; Kong, Yefu; Wang, Linlong; Kang, Bin (Frontiers in Ecology and Evolution, 2022)
In recent years, Harpadon nehereus gradually become a dominant species with great potential for exploitation in the East China Sea, and it is worth investigating whether H. nehereus would tolerate cold stress to continue to expand into the colder northern waters. The molecular regulation level is favorable evidence to explore the cold tolerance of H. nehereus, a total of 6650, 1936, and 2772 differentially expressed genes (DEGs) in transcription regulation, and 4409, 1250, and 2303 differential alternative splicing genes (DASGs) in alternative splicing regulation were identified in H. nehereus at 13℃, 15℃, and 17℃ respectively, importantly, 47 genes were identified as the key candidate genes for cold tolerance in H. nehereus. In transcription regulation, up-regulated DEGs were enriched in metabolic process terms and ribosome, spliceosome pathway, etc., while down-regulated DEGs were enriched in signal transduction terms, focal adhesion, proteoglycans in cancer pathway, etc., at 13℃, 15℃, and 17℃, respectively. In alternative splicing regulation, spliceosome, mRNA surveillance pathway, etc., were significantly enriched in DASGs. In a word, H. nehereus adapts to cold environments mainly through transcription and translation, transmembrane transport, protein modification, etc., while cold stress may also induce some diseases in H. nehereus.